Impact of the T296S mutation in P450 GcoA for aryl-O-demethylation: a QM/MM study - Santos, Sonia F. G.; Bommareddy, Rajesh Reddy; Black, Gary W.; Singh, Warispreet (Frontiers in Chemistry, 2024)
Lignin, a complex plant cell wall component, holds promise as a renewable aromatic carbon feedstock. p-Vanillin is a key product from lignin depolymerization and a precursor of protocatechuic acid (PCA) that has a tremendous potential for biofuel production. While the GcoAB enzyme, native to Amycolatopsis sp., naturally catalyses aryl-O-demethylation toward Guaiacol, recent research introduced a single mutation, T296S, into the GcoAP450 enzyme, enabling it to catalyse aryl-O-demethylation of p-vanillin. This structural modification increases the efficiency of GcoAP450 for natural substrate while being active for p-Vanillin. This study reveals the increased flexibility of p-Vanillin and its ability to adapt a favorable conformation by aligning the methoxy group in close vicinity of Fe(IV)=O of Cpd I in the active site of T296S variant. The QMMM calculations in accordance with the experimental data validated the rate limiting step for the oxidation of p-Vanillin is hydrogen atom abstraction and provided the detailed geometric structure of stationary and saddle points for the oxidation of p-Vanillin.